Islamic Guidance for Darullughah Wadda'wah Bangil Pasuruan Islamic Boarding School Students - Ilhamuddin, Muhammad Farid (Al Musyrif: Jurnal Bimbingan dan Konseling Islam, 2023)
Today's youth are still far from the teachings taught by Rasulullah SAW. This is due to progress and development in various fields, while the development of conscience or religious education has received less portion. At the same time, formal educational institutions give priority to general education. The consequence is that the culture that is spread is not only a culture that is in accordance with religious values, but also a culture that has the potential to damage the nation's morals. This type of research is qualitative research. This research was conducted at the Darullughah Wadda'wah Islamic Boarding School with the subjects asatidzah senior, teaching staff asatidzah, and senior santri/ORSADA. The research sample consisted of Darullughah Wadda'wah Islamic boarding school students. Methods of data collection using interview guidelines. Data analysis techniques using descriptive qualitative analysis. The result of this research is that the guidance of the Prophet's method at the Darullughah Wadda'wah Islamic Boarding School Bangil Pasuruan produced good results. This can be seen from several alumni and senior students who are able to take part and interact with people around them. They become preachers in their respective areas and all of this is thanks to the coaching efforts carried out at Islamic boarding schools. Because the development of character and knowledge is able to raise the good name of each of them, so that they can enter any circle.